The Problems in the Implementation of Inclusive Education in Primary Schools - Ediyanto, Ediyanto; Ramadhani, Risa Safira; Fitrasari, Bella Dina; Kenila, Elisabet; Sunandar, Asep; Hastuti, Wiwik Dwi; Suhendri, Suhendri (Department of Special Education, 2023)
Inclusive education is an educational service that provides opportunities for children with SEN to attend regular schools with their peers. Inclusive education is also a form of Education for All. The implementation of inclusive education has been implemented at the primary school level. However, in its implementation, inclusive education still finds problems. The purpose of this study was to analyze the problems of implementing inclusive education in primary schools. This research study goes through three stages: determining the scope that will focus on the research, determining the urgency and novelty of the research, and determining the research formulation and objectives. A total of sixteen journal articles from 2011 until 2020 with the topic of problems in implementing inclusive education in primary schools. This literature is collected through the Google Scholar database. Based on the current literature review, the problems that exist in the implementation of inclusive education in primary schools are found in the aspects of teacher understanding or skills in teaching SEN students, school infrastructure, student attitudes with the presence of SEN students in the same class, the role of parents, implementation of learning and curriculum development, fees procurement, and cooperation with various parties.